The document: The text of the deposition (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The medical doctor Melchiorre Allegra tells the pubblic authority at 1937, during the fascism, the structure and network of the organisation Cosa Nostra. The text, which was found incomplete, prove to be an important preview of Tommaso Buscetta’s admission. Keywords: Mafia, Fascism, Allegra, De Mauro, “L’Ora”